High Performance Leadership and its Relationship with the Organizational Climate in a Peruvian Company in the Industrial Sector in Lima, 2021 - Pereyra Lazo, Edson Joao (2022)
The main objective of this study was to determine the level of relationship between high performance leadership and organizational climate in a population of 280 workers of a Peruvian company in the industrial sector dedicated to modular construction. A total of 108 people who exercised some type of leadership according to the nature of their position was identified. The study was applied to the entire group by means of an analysis with Likert-type surveys. According to the results, the variable “high performance leadership” and “organizational climate” are significantly and positively correlated (0.812). The dimensions of the variable “high performance leadership” are “personal leadership”, “relational leadership” and “organizational-strategic leadership”. In the case of the dependent variable “organizational climate”, the dimensions are “personal factors”, “relational-group factors” and “organizational factors”. It is concluded that high performance leadership and all its dimensions are related to organizational climate.